Еxactness of sawing of saw-timbers on horizontal ribbon sav machine-tools - Shostak, Volodymyr; Puna , Volodymyr (Forestry, Forest, Paper and Woodworking Industry, 2007)
The results of researches are described conducted in the terms of productions. Equalization of regression, characterizing dependence of the field of dispersion of thickness of saw-timbers on a serve on a blade and cutting ways, is got. Showed out a formula for the calculation of possible speed of serve after exactness of sawing.